Identifying Demographic and Academic Issues that Influence the Passing or Failing of the Physiology Course in the Medicine Study Program of UCIMED (University of Medical Sciences) - Vanegas-Pissa, Juan Carlos (2015)
(This paper, product of a research project, analyzes some academic and demographic issues that might influence students passing or failing Physiology in the Licentiate Study Program in Medicine and Surgery at UCIMED (University of Medical Sciences) between 2008 and 2011. This was a retrospective cohort study. We analyzed the grades obtained by the students who were taking Physiology for the first, second or third time during the research period, the semesters in which the grades were obtained, who passed or failed the course, their sociodemographic characteristics, and other courses passed or failed previously with their corresponding grades. For the data analysis, we used the Stata 13 software (Data Analysis and Statistical Software) with a logistic regression model to determine the variables, which explain the passing or failing of the Physiology course. The results showed that the variables with a greater effect on the probability of p